PID CONTROL FOR AUTONOMOUS OBJECT-FOLLOWING ROBOT - Nguyen, Duc-Bao-Long; Ho, Minh-Khoi; Dao, Anh-Quan; Truong, Nhu-Bao; Nguyen, Thanh-Binh; Nguyen, Quang-Trung; Nguyen, Hoang-Nghia; Nguyen, Dang-Khoi; Le, Quang-Hung; Tran, Ky-Tinh (Indonesian Journal of Engineering and Science, 2025)
This paper presents an experimental study on the PID algorithm applied to a vehicle system that maintains a fixed distance from an object. The research focuses on how changes in PID parameters affect the vehicle's behavior. The system comprises an SRF05 ultrasonic sensor connected to an Arduino, controlling the vehicle is forward and backward movements to follow the object. Through a series of experiments, analyses, and evaluations, the study explores the effectiveness of the PID controller and addresses challenges. The results help identify the optimal PID parameter values for the system systematically.